2001
DOI: 10.1038/sj.gt.3301343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adenoviral fiber mutations on viral encapsidation, infectivity and in vivo tropism

Abstract: Targeting of adenovirus (Ad)-encoded therapeutic genes to specific cell types has become a major goal in gene therapy. Redirecting the specificity of infection requires the abrogation of the natural interaction between the viral fiber and its cellular receptors (CAR) and the simultaneous introduction of a new binding specificity into the viral capsid. To abrogate the natural affinity of the fiber, we have mutated residues presumed to be directly or indirectly involved in CARbinding in the knob domain of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 46 publications
3
71
1
Order By: Relevance
“…One way to do this rationally is by designing point mutants that disrupt undesired binding to certain receptors and promote the binding to others. To this end, elimination of CAR binding by HAd5 fiber has already been achieved (71,72). In this work, we identify point mutants of CAV-2 and HAd37 fiber heads with greatly reduced ability to bind immobilized CAR D1.…”
mentioning
confidence: 97%
“…One way to do this rationally is by designing point mutants that disrupt undesired binding to certain receptors and promote the binding to others. To this end, elimination of CAR binding by HAd5 fiber has already been achieved (71,72). In this work, we identify point mutants of CAV-2 and HAd37 fiber heads with greatly reduced ability to bind immobilized CAR D1.…”
mentioning
confidence: 97%
“…9,10 Ad5 vectors with the S408E mutation are unable to directly interact with CAR. 9,11 The deletion of the RGD (Arg-Gly-Asp) motif within the penton base was shown to affect not only binding to a v integrin and the subsequent internalization 12 but also the escape of viral particles from the endosomes. 13 Whereas the infection efficiency of Ad5 vectors with the S408E mutation or RGD deletion in cell culture was severely reduced, the liver tropism of these vectors in vivo remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…13 Whereas the infection efficiency of Ad5 vectors with the S408E mutation or RGD deletion in cell culture was severely reduced, the liver tropism of these vectors in vivo remained unchanged. 9, 10 Smith et al 14 have described the putative HSPG ablating mutation S* with the Lys-Lys-Thr-Lys (KKTK) motif in the fiber shaft being changed to Gly-Ala-Gly-Ala (GAGA). Reduced gene transfer with the resulting vector was not only seen in vitro but also in vivo with 15-fold reduced liver transduction after systemic application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that ablation of CAR binding does not alter the biodistribution or toxicity of systemically administered adenovirus in mice. 10,11 In both studies, the biodistribution was monitored by Q -PCR and transgene expression assays. A more recent report has demonstrated that a CAR -ablated vector with the KO1 mutation in the AB loop gave higher levels of hepatic gene transduction than vectors containing wild -type fiber.…”
Section: Virus Retargeting Strategiesmentioning
confidence: 99%